2007
DOI: 10.1002/eji.200636625
|View full text |Cite
|
Sign up to set email alerts
|

IL‐13 induces expression of CD36 in human monocytes through PPARγ activation

Abstract: The class B scavenger receptor CD36 is a component of the pattern recognition receptors on monocytes that recognizes a variety of molecules. CD36 expression in monocytes depends on exposure to soluble mediators. We demonstrate here that CD36 expression is induced in human monocytes following exposure to IL-13, a Th2 cytokine, via the peroxisome proliferator-activated receptor (PPAR)c pathway. Induction of CD36 protein was paralleled by an increase in CD36 mRNA. The PPARc pathway was demonstrated using transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 52 publications
(75 reference statements)
7
69
1
Order By: Relevance
“…In conclusion, the present results support our previous in vitro work showing that IL-13 positively regulates macrophage MR surface expression partly by controlling the production of PPAR␥ endogenous ligand, 15d-PGJ 2 , via a cPLA 2 activation both in mouse (6) and in human monocytes (37). It shows the in vivo importance of the nuclear receptor PPAR␥ in the reduction of esophageal and GI candidiasis in immunocompetent and immunodeficient RAG-2 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In conclusion, the present results support our previous in vitro work showing that IL-13 positively regulates macrophage MR surface expression partly by controlling the production of PPAR␥ endogenous ligand, 15d-PGJ 2 , via a cPLA 2 activation both in mouse (6) and in human monocytes (37). It shows the in vivo importance of the nuclear receptor PPAR␥ in the reduction of esophageal and GI candidiasis in immunocompetent and immunodeficient RAG-2 Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 90%
“…PPAR␥ is a nuclear receptor initially linked to the regulation of adipogenesis in fat tissue (36). It was previously shown that PPAR␥ can regulate monocyte gene expression and differentiation (16), and that IL-4, and more recently IL-13, induce the expression of the type B scavenger receptor CD36 through PPAR␥ activation (16,(37)(38)(39), hence facilitating the phagocytosis of Plasmodium falciparum-parasitized erythrocytes (37) and to decreasing malaria-induced TNF-␣ secretion (40). In addition to CD36 overexpression, PPAR␥ plays a critical role in the regulation of cholesterol homeostasis by controlling the expression of a network of genes that mediate cholesterol efflux from cells and its transport in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data have revealed the pivotal role exerted by increased PPARc in positively modulating CD36 expression in macrophages in response to different stimuli such as oxLDL [14,23] or cytokines [24]. Thus we evaluated whether the observed up-regulation of CD36 in 3T3-L1 cells was somehow related to oxLDL effects on PPARc activity.…”
Section: Effects Of Oxldl On the Expression And Activity Of Pparcmentioning
confidence: 97%
“…There is a considerable literature describing the activation of PPAR ␥ by 12/15-LOX metabolites and, thus, the induction of PPAR ␥ itself and target gene expression in multiple cells and tissues ( 28,30,31 ). These data prompted us to examine the possible link of them in brain tissue in the setting of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Another PPAR ␥ agonist, rosiglitazone, also shows potent anti-infl ammatory actions following transient focal ischemia by inhibiting the expression of pro-infl ammatory proteins, myeloperoxidase and intercellular adhesion molecule-1 (ICAM-1), and reduced neutrophil accumulation ( 25 ). Recently, it has been found that 12(S)-and 15-(S)-HETE can function as ligands of PPAR ␥ in the cells derived from outside the CNS (28)(29)(30)(31)(32). However, whether they can regulate PPAR ␥ following brain ischemia is still unknown.…”
Section: Western Blot Analysismentioning
confidence: 99%